Cross‐cultural comparison of predictors for self‐care behaviors in patients with type 2 diabetes. Issue 5 (23rd March 2018) - Ikeda, Kaori; Fujimoto, Shimpei; Morling, Beth; Ayano‐Takahara, Shiho; Harashima, Shin‐ichi; Uchida, Yukiko; Inagaki, Nobuya
Abstract: The aim of the present study was to evaluate how culture moderates the behavioral and psychosocial predictors of diabetes self‐care activities. Patients with type 2 diabetes were recruited in the outpatient department at two sites: Kyoto University hospital in Japan and the Christiana Care Health System in the USA. The data were collected by survey using questionnaires including questions on the frequency of self‐care activities, behavioral and psychosocial predictors, and other background information from 149 Japanese patients and 48 American patients. The cultural impact was observed by multiple regression analyses with interaction terms on the association between emotional support and self‐care activities in diet in female patients. The findings of the present study serve as an example of how cultural context can affect patients with diabetes, and lead to a better understanding of culturally sensitive behavioral intervention. Abstract : Emotional support was a stronger predictor of diabetes self‐care activities than diabetes‐related distress in Japanese female patients. On the other hand, in American female patients, diabetes‐related distress was the strongest predictor of self‐care activities. These findings serve as an example of how cultural context can affect patients with diabetes.